Pre-argumentative reasoning - Novais, Paulo (2005)
Intelligent agents configure a new generation of virtual entities that perform various autonomous tasks on behalf of others, namely the humans. On the other hand, the information society requires the development of new and more intelligent methods, tools and theories to analyse, define, model and specify agent-based systems. It is under this presupposition that in this work are introduced a pre-argumentative reasoning scheme, which need to be able to take into account, in a negotiation, factors such as temporality, priority, delegation, gratitude and agreement, enabling the agents to react and pro-act accordingly. This argument-based negotiation among agents has much to gain from the use of Extended Logic Programming and Incomplete Information, in terms of the argument’s evaluation. Indeed, it is based on this substratum that are presented the bases for a pre-contract negotiation via argumentation, where pre-contract negotiation will be defined as a protocol which, once enforced, will allow the exchange of messages containing proposals, counter-proposals, critiques, justifications or even explanations. The terms of a negotiation are also set, adjusting the contract according to the agent’s knowledge base. In fact, an important contribution of this work relies on the presentation of the basic definitions and the general model of pre-contract-based negotiations via argumentation.